Relational development in online friendships in Singapore. - Chua, Hern Cheng. (2008)
This research examines the viability of using computer-mediated communication in the development of interpersonal relationships. Essentially, we will be investigating how social actions and communication behavior metamorphose as they are refracted through online interactions. The patterns of online interaction observed will then facilitate us to analyze and assess the quality of personal relationships forming in the virtual world.